If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 30 = a(a + -7) Reorder the terms: 30 = a(-7 + a) 30 = (-7 * a + a * a) 30 = (-7a + a2) Solving 30 = -7a + a2 Solving for variable 'a'. Reorder the terms: 30 + 7a + -1a2 = -7a + 7a + a2 + -1a2 Combine like terms: -7a + 7a = 0 30 + 7a + -1a2 = 0 + a2 + -1a2 30 + 7a + -1a2 = a2 + -1a2 Combine like terms: a2 + -1a2 = 0 30 + 7a + -1a2 = 0 Factor a trinomial. (10 + -1a)(3 + a) = 0Subproblem 1
Set the factor '(10 + -1a)' equal to zero and attempt to solve: Simplifying 10 + -1a = 0 Solving 10 + -1a = 0 Move all terms containing a to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -1a = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -1a = 0 + -10 -1a = 0 + -10 Combine like terms: 0 + -10 = -10 -1a = -10 Divide each side by '-1'. a = 10 Simplifying a = 10Subproblem 2
Set the factor '(3 + a)' equal to zero and attempt to solve: Simplifying 3 + a = 0 Solving 3 + a = 0 Move all terms containing a to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + a = 0 + -3 Combine like terms: 3 + -3 = 0 0 + a = 0 + -3 a = 0 + -3 Combine like terms: 0 + -3 = -3 a = -3 Simplifying a = -3Solution
a = {10, -3}
| 6x-3-6x+8=11x | | -4q+3q=-6 | | 30x=5 | | 3-4=-1 | | -5.3=2.2v-86 | | 9(4-y)+2=-2(y-2)-3 | | x+3-9x=9x-31-9x | | 3(2x)+5x=11 | | 14x-15=11x-13 | | 18(x+3/18)=18(7/9+x-5/2) | | x+3/18=7/9+x-5/2 | | 4x^2-x+42=0 | | x/3=x/4-6 | | 20x^2-95x-315=0 | | 10y-(y)(y)=40 | | 2x+36=624 | | 18x^2+7x-10=0 | | x^4+8x^3+6x^2=0 | | 10-(y)(y)=40 | | -5=4x-(3x-7) | | 7(2y-5)-8y=1 | | x^4+22x+121=0 | | 7a-2a=45 | | 3x^2+4y=12 | | 7x=6x-630 | | 18=8+b+8 | | 3-[2x+3(x-5)]= | | (x-4)(x+7)=2(x-4) | | -(7y+2)-(-6y-8)=-1 | | -(7y+2)-(6y-8)=-1 | | Y=.4x+b | | -(7y+2)-(-6-8)=-1 |